Significances of Collimator Angle Rotation and Different Angle Combinations in Volumetric-Modulated Arc-Based Stereotactic Radiosurgery With 5-mm Leaf-Width Multileaf Collimator for Single Brain Metastases - Ohtakara, Kazuhiro; Suzuki, Kojiro (Curēus (Palo Alto, CA), 2025)
Purpose In linac-based stereotactic radiosurgery (SRS) using a multileaf collimator (MLC) for multiple brain metastases (BMs), the appropriate MLC angle rotation is useful to minimize the intervening brain dose by avoiding island blocking between the lesions localized along the direction of leaf movement. However, in some linac systems, the MLC angle cannot be rotated, or the cephalad rotation range of non-coplanar arcs (NCAs) is severely limited. In addition, the significance of MLC angle rotation has yet to be clarified in SRS for single BMs. This planning study was therefore conducted to investigate the significances of MLC angle rotations and the different angle combinations in SRS with a 5-mm leaf-width MLC for single BMs using volumetric-modulated arcs (VMA) consisting of one coplanar arc and two NCAs rotated 60º cranially. Materials and methods The study subjects were 30 lesions in 27 patients with the gross tumor volume (GTV) ranging from 0.08 cc to 48.09 cc (median 9.81 cc). Four VMA-based SRS plans were created for each GTV using an Agility MLC (Elekta AB, Stockholm, Sweden) and a planning system Monaco (Elekta AB). The VMA optimization was based on a previously established method with identical settings except for the MLC angle rotation for the three arcs: no rotations (all 0º, All_0), all 90º (All_90), all 45º (All_45), and a combination of 0º, 45º, and 90º (0_45_90). 43.000 Gy in five fractions was uniformly prescribed to each GTV , the minimum dose to encompass the GTV minus 0.01 cc ( ), for GTV >0.20 cc or for GTV ≤0.20 cc. The planning parameters of a total of 120 plans were compared. Results There was no significant difference in any parameter between the four groups in Friedman's test. The individual comparisons between the two groups using the Wilcoxon signed-rank test revealed significant differences only in the following four parameters: (1) the GTV coverage by the , the minimum dose of the irradiated isodose volume (IIV) equivalent to each target volume; (2) the at 2 mm outside the GTV boundary; (3) the IIV spillage receiving ≥75% of the prescribed dose; and (4) the coverage value at 2 mm inside the GTV boundary. Overall, the All_45 showed the best tendency between the three groups with the specific fixed MLC angle. Regarding the prescribed isodose volume (PIV) spillage outside the GTV, the median and third quartile values were smallest in the All_45, and the maximum value ​​was smallest in the 0_45_90. The maximum difference in the PIV spillage was 0.52 cc between the 0_45_90 (smallest) and the All_45. Conclusions An MLC angle rotation and the different combinations can improve dose distribution in VMA-based SRS even for single BMs, and the optimal rotation angle differs for individual lesions. VMA without MLC angle rotation (all 0º) can provide an overall non-inferior dose distribution in the three-arc arrangement that divides the cranial hemisphere into thirds. When selecting a fixed MLC angle for efficient irradiation, 45º is recommended among 0º, 90º, and 45º. Further study is required to find criteria for determining the appropriate MLC angle for each lesion.